Comprehensive structure of novel voice priority queue scheduling system model for VoIP over WLANs - Nisar, Kashif; Amphawan, Angela; Hassan, Suhaidi (IGI Global, 2013)
Voice over Internet Protocol (VoIP) has grown quickly in the world of telecommunication.Wireless Local Area Networks (WLANs) are the most performance assuring technology for wireless networks, and WLANs have facilitated high-rate voice services at low cost and good flexibility. In a voice conversation, each client works as a sender or a receiver depending on the direction of traffic flow over the network.A VoIP application requires high throughput, low packet loss, and a high fairness index over the network.The packets of VoIP streaming may experience drops because of the competition among the different kinds of traffic flow over the network.A VoIP application is also sensitive to delay and requires the voice packets to arrive on time from the sender to the receiver side without any delay over WLAN.The scheduling system model for VoIP traffic is an unresolved problem. The objectives of this paper are to identify scheduler issues.This comprehensive structure of Novel Voice Priority Queue (VPQ) scheduling system model for VoIP over WLAN discusses the essential background of the VPQ schedulers and algorithms.This paper also identifies the importance of the scheduling techniques over WLANs.